Hydroxyapatite coatings for biomedical applications - Zhang, Sam. (Boca Raton : CRC Press, 2013)
"This handbook covers developments in processing and property characterization and applications of Hydroxyapatite (HA), providing a timely resource for active researchers and newcomers to the field. It details HA coatings and use in dental implants, biomimetic HA materials, electrochemical and pulsed laser deposition, drug delivery, and more. In an approach that differs from traditional handbooks, it contains more than just data such as tables and figures. It is written in such a way that seasoned professionals at every level will find it a valuable data source that gives them indispensable help in their research"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Biomedical materials; Hydroxyapatite coating -- Therapeutic use; Electronic books